2020
DOI: 10.1155/2020/6140728
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Key Modules, Hub Genes, and Noncoding RNAs in Chronic Rhinosinusitis with Nasal Polyps by Weighted Gene Coexpression Network Analysis

Abstract: Chronic rhinosinusitis with nasal polyps (CRSwNP) is a chronic inflammatory disease with relatively easy recurrence. However, the precise molecular mechanisms of this disease are poorly known. Based on gene sequencing data obtained from the Gene Expression Omnibus (GEO) database, we constructed coexpression networks by weighted gene coexpression network analysis (WGCNA). Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) enrichment analyses were performed by the Database for Annotation, Visu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…Although previous studies involved bioinformatic analysis of mRNAs and lncRNAs in CRSwNP (Liu et al, 2019 ; Zhou et al, 2020 ), one study included only 12 CRSwNP patients and 9 healthy controls. The other study used nasal tissue data combined with primary human basal cells cultured in an air-liquid interface system, which might be different from nasal polyp tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Although previous studies involved bioinformatic analysis of mRNAs and lncRNAs in CRSwNP (Liu et al, 2019 ; Zhou et al, 2020 ), one study included only 12 CRSwNP patients and 9 healthy controls. The other study used nasal tissue data combined with primary human basal cells cultured in an air-liquid interface system, which might be different from nasal polyp tissue.…”
Section: Discussionmentioning
confidence: 99%
“…By applying WGCNA, detailed characteristics have been investigated at the genetic network level 15 . This framework has been successfully utilized to study different cancers and non-cancer diseases 16,17 .Finding co-expression patterns can also associate the unknown function genes with biological processes due to the guiltby-association (GBA) basis of WGCNA.…”
mentioning
confidence: 99%
“…This novel transcript has been demonstrated to play important roles in a wide range of biological processes in humans. Recent studies have demonstrated the vital role of lncRNAs in CRSwNP, and some of these lncRNAs may be potential biomarkers for diagnosis and therapeutic targets 32 , 54 . The competing endogenous RNA (ceRNA) hypothesis proposed by Salmena et al in 2011 pointed to lncRNAs acting as endogenous molecular sponges that competitively bind miRNAs via shared MREs with reverse complementary binding seed regions to indirectly regulate mRNA expression levels 24 .…”
Section: Discussionmentioning
confidence: 99%